A comprehensive study on force, temperature, mechanical properties and micro-structural characterizations in friction stir lap welding of dissimilar materials (AA6061-T6 & AISI304). (January 2018) - Mahto, Raju Prasad; Kumar, Ravi; Pal, Surjya K; Panda, Sushanta K
Abstract: Friction stir welding has been used to produce a lap joint between aluminum alloy AA6061-T6 and stainless steel AISI 304. The effect of welding and rotational speeds on axial force, weld temperature and mechanical properties such as ultimate tensile strength and fractography has been investigated. In addition, an interface metallurgical characterization has been carried out for various process parameters which indicated that the TMAZ is affected by the hooking effect. Further, the fractography study on the fracture surface has shown quasi-cleavage fracture at lower values of rotational and welding speeds, whereas ductile mode of fracture is observed at higher values of rotational and welding speeds. Point EDS and line scan results on the interface indicated the formation of inter-metallic compounds of aluminum, iron and chromium of thickness ∼12 μm. XRD results revealed the formation of FeAl, Fe2 Al5 and AlFe2 Cr. But the most notable result is that the fracture occurred outside the weld region which indicated that a thinner inter-metallic compound did not have a detrimental effect to the weld strength.